Challenges of Deployment of ICT Facilities by Post-Basic Education and Career Development (PBECD) During Covid-19 in Nigeria - Ogunode Niyi. Jacob; OkweloguIzunna Somadina; Olatunde-Aiyedun, T. G. (International Journal on Human-Computing Studies, 2021)
The covid-19 pandemic since it advent in 2019 have affected the traditional conventional method of teaching and learning in all educational institutions across the world. The sudden switch over to online education by countries was easy for some advanced countries while developing countries faced with numerous challenges. Nigeria, which is one of the developing country in Africa and the world faced many challenges of deploying information communication technologies for teaching and learning during the covid-19 lock down. This paper wish to discuss the challenges faced by Post-Basic Education and Career Development (PBECD) in the deployment of ICT for teaching and learning during covid-19 lock down. Secondary data was used to support the various facts raised in the discussion. The findings revealed that the following are the major challenges or problems faced during the covid-19 era: inadequate funding, unstable power supply, high cost of ICT facilities, poor computer literacy among teachers and students, inadequate ICT professionals, inadequate ICT infrastructural facilities in schools and poor implementation of ICT educational policies. Based on this findings, it was recommended that government should provide adequate fund in education so as to ensure that online education are fully integrated into the Nigerian educational system.